Regenerasi Penari dan Penabuh dalam Seni Reog Obyok di Tanah Laut, Kalimantan Selatan: Regeneration of Dancers and Drummers in Reog Obyok Art in Tanah Laut, South Kalimantan - Indriyani, Putri Dyah; Nurdiyana, Tutung; Sari, Putri Yunita Permata Kumala (​Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
This study examines the patterns of dancer and drummer regeneration within the Reog Obyok art group in Tanah Laut Regency, South Kalimantan. Regeneration is crucial in the sustainability of traditional performing arts, especially in transmigrant communities facing cultural and social challenges. This research employs a descriptive qualitative approach with data collection techniques such as participatory observation, in-depth interviews, and visual documentation. The findings reveal that the regeneration process occurs informally through a familial approach, the inheritance of oral traditions, and community-based training. However, regeneration faces several challenges, including the low interest of the younger generation, limited facilities, and minimal institutional support. This study emphasizes the importance of strengthening a community-based regeneration system that is adaptive to the local socio-cultural context.